Cameron and Liberal Conservatism: Attitudes within the Parliamentary Conservative Party and Conservative Ministers. (August 2013) - Heppell, Timothy
Research Highlights and Abstract This article: Contributes to the development of academic research on the internal dynamics of the Conservative Party under the leadership of David Cameron. Contributes to the development of academic research on the processes of ministerial selection within British Government. Contributes to the development of academic research on cohort effects within parties, and the analysis of comparisons and differences between different parliamentary cohorts. Contributes to the development of academic research on the constraints upon Prime Ministerial power when in coalition. This article identifies the ideological composition of the parliamentary Conservative party (PCP) in order to determine the location and numeric strength of the critics of Cameron. By constructing a data set of attitudes across two ideological divides—the social, sexual and morality divide and the European divide—the article identifies the following. First, despite Cameron's social liberal emphasis both the PCP and his ministerial team is predominantly Thatcherite—i.e. socially conservative. Second, despite numerically having a Eurosceptic PCP and ministerial team, with Europhilia now an inconsequential rump, Cameron faces a minority 'hard' Eurosceptic faction of rebels who oppose his 'soft' Euroscepticism. Third, the influx of new parliamentarians elected in 2010 may increase social liberal strength, but they are overwhelmingly Eurosceptic, with a significant tranche of hard Eurosceptics amongst them. Finally, through a process of ideological mapping of these two ideological divides the research identifies a core of 50 socially conservative and hard Eurosceptics who are the critics of Cameron.